2022
DOI: 10.1186/s13045-022-01378-1
|View full text |Cite
|
Sign up to set email alerts
|

FIT-based risk-stratification model effectively screens colorectal neoplasia and early-onset colorectal cancer in Chinese population: a nationwide multicenter prospective study

Abstract: No fully validated risk-stratification strategies have been established in China where colonoscopies resources are limited. We aimed to develop and validate a fecal immunochemical test (FIT)-based risk-stratification model for colorectal neoplasia (CN); 10,164 individuals were recruited from 175 centers nationwide and were randomly allocated to the derivation (n = 6776) or validation cohort (n = 3388). Multivariate logistic analyses were performed to develop the National Colorectal Polyp Care (NCPC) score, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…48 Most patients visit hospitals due to minor GI symptoms without any alarm symptoms. 17 systemic symptoms, and history of aspirin use. 49 However, this score is too complex, which limits its clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…48 Most patients visit hospitals due to minor GI symptoms without any alarm symptoms. 17 systemic symptoms, and history of aspirin use. 49 However, this score is too complex, which limits its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was no significant difference in the incidence of CRN between symptomatic patients and asymptomatic individuals (23.3% vs 20.4%, P = 0.190), which is consistent with previous studies. 17 Previous studies have analyzed the diagnostic value of the combination of multiple symptoms for CRC, 15 and that the combination of symptoms defined by age has more diagnostic value than individual symptoms. 50 At present, studies mainly focused on the diagnostic value of rectal bleeding in symptomatic patients, but less on non-specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations